The Rollout of GST and its Impact on the Auto Sector Stocks of National Stock Exchange - Muthukamu, M.; Amudha, R. (Indian Journal of Finance, 2020)
The most awaited and the biggest indirect tax reform in India – Goods and Services Tax (GST) was finally introduced on July 1, 2017. On contrary to the expectations, the automobile industry had severe hiccups during the latter part of 2018, and experienced negative sales growth and the people were jittery about the process of implementation of GST in India. The present study was dedicated to assess and compare the returns rendered by the auto sector stocks listed in the Indian equity market, pre-and postimplementation of GST in India and to understand the level of volatility in the price behaviour of the selected stocks during the study period. To achieve this, we used the daily closing prices of the constituent stocks of auto sector index of National Stock Exchange for 90 trading days pre and post the execution of GST (from February 20, 2017 – November 9, 2017) and relevantly applied the GARCH family models to understand the existence and extent of symmetric and asymmetric volatility in the auto sector stocks. We found that the implementation of GST in India showed a negative impact on the returns delivered by the auto sector stocks and also found abnormal and heightened volatility during the post GST period.